2015
DOI: 10.1371/journal.pone.0125275
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Bilirubin and Left Ventricular Hypertrophy in Patients with Essential Hypertension

Abstract: BackgroundProspective studies have found low bilirubin levels were an important predictive factor of cardiovascular events. However, few have yet investigated possible association between serum bilirubin level and LVH in essential hypertension. The aim of the present study was to evaluate the relationship between serum bilirubin levels with LVH in newly diagnosed hypertension patients.MethodsThe present study evaluated the relationship between serum total bilirubin level and left ventricle hypertrophy (LVH) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We found that bilirubin concentration was decreased in carriers of the pathogenic DCM variants [ 43 ]. In agreement with our results, previous studies have shown that bilirubin concentrations are significantly decreased in patients with heart failure [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…We found that bilirubin concentration was decreased in carriers of the pathogenic DCM variants [ 43 ]. In agreement with our results, previous studies have shown that bilirubin concentrations are significantly decreased in patients with heart failure [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…The reason may be that the patients with overt cardiovascular disease were excluded and that few patients took ACE inhibitors or β-blockers in this study. Additionally, a previous study showed that serum bilirubin concentrations were inversely correlated with LVMI in the patients with hypertension who had not received any treatment [ 26 ]. In that study, hypertensive patients with diabetes mellitus were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, oxidant-mediated heme oxygenase induction provides feedback control of oxidative stress [ 132 ]. Recent evidence that serum bilirubin correlates inversely with risk for LVH in hypertensives, independent of blood pressure, may reflect the ability of free bilirubin to blunt the contribution of Nox-mediated oxidative stress to the progression of VH [ 135 , 136 ]. Moreover, induction of heme oxygenase-1 activity opposes induction of VH in rats that are hypertensive or treated with angiotensin II [ 137 , 138 ].…”
Section: Attenuating Oxidative Stressmentioning
confidence: 99%